A Worthy Heir: Donald Trump, the Republican Party and Climate Change - Jean-Daniel Collomb (Revue LISA)
The aim of this article is to demonstrate that Donald Trump’s commitment to climate skepticism and his hostility toward the very idea of a proactive federal apparatus of environmental regulation do not mark a departure from Republican and conservative orthodoxy but, rather, signal his adherence to positions developed and refined by the libertarian and free-market conservative think tanks that have been supplying the Republican Party with ideas and policy proposals since the 1970s. The article underscores the high degree of continuity between President Trump’s approach to climate change and the environmental policies implemented by his Republican predecessors since Ronald Reagan, which have revolved around a preference for market solutions over government regulations, deep mistrust of environmental multilateralism, efforts to increase fossil fuel production on public lands, and attempts to restrict access to environmental and climate data.